The Era of Cytotoxic CD4 T Cells - Cenerenti, Mara; Saillard, Margaux; Romero, Pedro; Jandus, Camilla (Frontiers in Immunology, 2022)
In 1986, Mosmann and Coffman identified 2 functionally distinct subsets of activated CD4 T cells, Th1 and Th2 cells, being key in distinct T cell mediated responses. Over the past three decades, our understanding of CD4 T cell differentiation has expanded and the initial paradigm of a dichotomic CD4 T cell family has been revisited to accommodate a constantly growing number of functionally distinct CD4 T helper and regulatory subpopulations. Of note, CD4 T cells with cytotoxic functions have also been described, initially in viral infections, autoimmune disorders and more recently also in cancer settings. Here, we provide an historical overview on the discovery and characterization of cytotoxic CD4 T cells, followed by a description of their mechanisms of cytotoxicity. We emphasize the relevance of these cells in disease conditions, particularly in cancer, and we provide insights on how to exploit these cells in immunotherapy.